Trust and willingness to pay for nanotechnology food. (April 2015) - Roosen, J.; Bieberstein, A.; Blanchemanche, S.; Goddard, E.; Marette, S.; Vandermoere, F.
Highlights: Trust in food safety is of high importance to consumers. More trusting consumers should exert lower self-protection effort. It is shown that WTP for new food characteristics increases with trust. WTP does not decrease as much with new information for high trusting consumers. Abstract: We analyze the role of trust in the evaluation of a new food technology, namely nanotechnology. A literature review in the social and economic sciences reveals that many different trust concepts are available. The economics literature suggests that trust can lead to lower efforts of self-protecting behavior. Translating this concept into the framework of willingness to pay (WTP) for food products allows for the derivation of hypotheses on the workings of trust. We show that WTP for new food characteristics increases with trust also when new information about the technology is revealed. The results are confirmed with online survey data for Canada and Germany and experimental data in Germany.